Correlation of Mental Toughness with Academic Achievement in Modern Pesantren Students in Aceh Indonesia/ Korelasi Mental Toughness dengan Prestasi Akademik pada Pelajar Pesantren Modern di Aceh Indonesia - Amna, Zaujatul; Safira, Syifa; Sari, Kartika; Faradina, Syarifah (Psikoislamika: Jurnal Psikologi Islam, 2020)
Abstract: Mental toughness is a capacity that individuals have in dealing with stressors, pressures, and challenges to achieve what they want. Individuals who have mental toughness will be able to overcome various kinds of demands and pressures that occur in their lives, one of which is in the field of education, such as academic achievement. This study aims to determine the correlation between mental toughness and academic achievement among Islamic boarding school students. A total of 335 students consisting of 219 women and 116 men with an age range of 12-18 years were selected as research samples using purposive sampling techniques. Mental Toughness Questionnaire-18 (MTQ-18) is used as a measure of mental toughness; meanwhile academic achievement is measured through score student report in period of Academic Year 2019/2020. The result has shown that there were positive and significant corelations between mental toughness and academic achievement in pesantren’s students (p= 0.011 with r= 0.139). In addition, the results of the study also suggested that the contribution of mental thougness toward on the students' academic achievement was lowest (1,9%). Further discussion of the correlation between the two variables has been described.Keywords: Mental Toughness; Academic Achievement; Boarding School StudentAbstrak: Mental toughness merupakan kemampuan yang dimiliki oleh individu dalam menghadapi stressor, tekanan, dan tantangan agar dapat mencapai tujuan yang dimiliki. Individu dengan mental toughness yang tinggi akan mampu mengatasi berbagai macam tuntutan dan tekanan yang akan dihadapinya, diantaranya adalah tuntutan yang akan ditemui dalam bidang pendidikan, seperti prestasi akademik. Penelitian ini bertujuan untuk mengetahui hubungan antara mental toughness dengan prestasi akademik pada pelajar pesantren modern. Sejumlah 335 pelajar yang terdiri dari 219 perempuan dan 116 laki-laki dengan rentang usia 12-18 tahun telah dipilih sebagai sampel penelitian dengan teknik purposive sampling. Mental Toughness Questionnaire-18 (MTQ-18) digunakan sebagai alat ukur mental toughness, sedangkan prestasi akademik diukur dengan menggunakan nilai rapor pelajar periode Semester Ganjil Tahun Ajaran 2019/2020. Hasil analisis menunjukkan bahwa terdapat hubungan yang positif dan signifikan antara mental toughness dengan prestasi akademik pada pelajar pesantren modern (p=0,011 dan r=0,139), artinya semakin tinggi tingkat mental toughness maka semakin tinggi pula prestasi akademik padapelajar pesantren modern tersebut. Selain itu, hasil penelitian ini juga menjelaskan bahwa nilai kontribusi variabel mental toughness terhadap prestasi akademik pelajar pesantren tergolong lemah, yaitu hanya 1,9%, pembahasan lanjutan mengenai korelasi antar kedua variabel tersebut telah diuraikan dalam artikel ini.Kata Kunci: Mental Toughness; Prestasi Akademik; Pelajar Pesantren